2017
DOI: 10.1038/s41531-017-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Using a smartphone-based self-management platform to support medication adherence and clinical consultation in Parkinson’s disease

Abstract: In the original version of this article the copyright notice was missing from Tables 1 and 3. This has now been added alongside the three relevant references inserted as refs. 21–23. The correction has been published and is appended to both the HTML and PDF versions of this paper. The errors have been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 2 publications
0
42
0
Order By: Relevance
“…In the third experiment, a smart device version of the test ("TapPD" developed by uMotif Limited for Apple [Cupertino, CA] iPhone and iPad devices) was used in addition to the keyboard test. 17,18 The same device was used for all participants. The participants used their index finger to alternately tap 2 target areas on the screen as fast and as accurately as possible for a period of 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…In the third experiment, a smart device version of the test ("TapPD" developed by uMotif Limited for Apple [Cupertino, CA] iPhone and iPad devices) was used in addition to the keyboard test. 17,18 The same device was used for all participants. The participants used their index finger to alternately tap 2 target areas on the screen as fast and as accurately as possible for a period of 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, patients can upload their information to the doctor through the application platform, strengthen their interaction with the doctor, adjust the medication plan in time, and strengthen the patient's self-management. The medication reminder function can increase medication compliance (19,32). Hu et al (19) also confirmed this point through their research in which 204 individuals with PD aged 52-87 were questioned about their attitudes toward self-management using smartphone applications, and the results were positive.…”
Section: Recent Findings On the Use Of Smartphone Apps For The Management Of Pdmentioning
confidence: 82%
“…However, their research also found that elderly people with high education and young people are more likely to accept smartphone applications for self-management. Furthermore, a multicenter randomized controlled trial by Lakshminarayana et al (32) described the positive effects of a 16-week smartphone application use on short-term self-reported medication compliance and quality of clinical consultation in individuals with PD.…”
Section: Recent Findings On the Use Of Smartphone Apps For The Management Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…A few smartphone applications have been developed to manage home-based medication and rehabilitation training for PD in China. An expert team composed of occupational therapists, graphic designers, and information technology experts has developed a mobile application called Care-PD, which has been tested and explored in reality (23). Based on previous experience, we have updated this application.…”
Section: Introductionmentioning
confidence: 99%